Permasalahan Spasial Ekonomi Pasca Pandemi Covid-19 di Kota Solo - Ali, Ilhaam; Rahma, Khoirida; Silviani, Silviani; Kusumawati, Lia (Jurnal Social Science, 2024)
The economy in Indonesia, which is mostly contributed by Micro, Small and Medium Enterprises (MSMEs), has experienced significant challenges since the outbreak of the global pandemic. The COVID-19 pandemic has had an impact on various sectors of life, including the economy and business. Solo City, as one of the economic centers in Central Java, cannot be separated from the challenges faced by Micro, Small and Medium Enterprises (MSMEs). This article aims to explore the changes in MSMEs in Solo City in dealing with the impact of the COVID-19 pandemic. The research method used is a descriptive qualitative approach. The distribution of MSME areas affected by the pandemic in Surakarta is uneven. The most affected areas are areas that rely on the tourism sector, such as Laweyan, Pasar Kliwon, and Jebres. The affected areas also include areas that rely on the trade sector, such as Pasar Gede, Pasar Kembang, and Pasar Beringharjo. Recommendations for strengthening MSMEs include increased government support, entrepreneurship education, technology infrastructure development, and business collaboration.